2021
DOI: 10.12669/pjms.37.2.3535
|View full text |Cite
|
Sign up to set email alerts
|

Focal Segmental Glomerulosclerosis in Paediatric Population of South Punjab Pakistan: A Tertiary Care Hospital Experience

Abstract: Objectives: To find out frequency, clinicopathological features, response of treatment and outcome among children with primary focal segmental glomerulosclerosis (FSGS). Methods: This retrospective, non-interventional medical charts review study was conducted from a period of January 2011 to January 2020 at Pediatric Department of Nishtar Medical University Hospital, Multan, Pakistan. During the nine years study period, children of both genders, aged less than 16 years, with renal biopsies proven FSGS we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Nephrotic syndrome was the most common indication in some, while SLE, nephritic syndrome, and other indications were reported in others. This variability concurs with previously published data internationally [28,29]. Primary glomerular diseases, particularly the primary ones, were found to be the most common pediatric renal diseases, accounting for 75.6% of all renal diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation

Overview of Nephrotic Syndrome in Arab Children: Systematic review

Amir Fayyaz Shaikh Sardar Muhammad,
Jamal H Alanezi,
Ibrahim Muqbil W Alanazi
et al. 2023
SMHJ
“…Nephrotic syndrome was the most common indication in some, while SLE, nephritic syndrome, and other indications were reported in others. This variability concurs with previously published data internationally [28,29]. Primary glomerular diseases, particularly the primary ones, were found to be the most common pediatric renal diseases, accounting for 75.6% of all renal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Studies also reported differences in the prevalence of FSGS, ranging from 15% to 59% [26,27]. FSGS was consistently reported as the primary underlying histopathology in children with SRNS in various studies [28]. Furthermore, the clinical indications for renal biopsies in different studies varied.…”
Section: Discussionmentioning
confidence: 99%

Overview of Nephrotic Syndrome in Arab Children: Systematic review

Amir Fayyaz Shaikh Sardar Muhammad,
Jamal H Alanezi,
Ibrahim Muqbil W Alanazi
et al. 2023
SMHJ
“…Focal segmental glomerulosclerosis is now one of the most common causes of nephrotic syndrome in pediatric and adult age groups [ 4 , 15 - 16 ] within the Pakistani population as shown by several studies. The prognosis is variable, with some patients going into remission while others progress to end-stage renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…FSGS is not a distinct clinical disease, rather it encompasses a large group of disorders that may result in this pattern of glomerular injury. The incidence of FSGS is on the rise and it is now one of the most common causes of steroid resistant-nephrotic syndrome in pediatric [ 3 - 4 ] and adult age groups [ 5 ], both worldwide and in the Pakistani population. It also has frequent progression to end-stage renal disease, with the literature citing [ 6 ] the African population as being particularly susceptible.…”
Section: Introductionmentioning
confidence: 99%